Perancangan Mebel Compact Multifungsi untuk Tempat Tinggal Berukuran Kecil - Ivi Claudya Kuswara; mariana wibowo (Intra, 2015)
As the number of landmass available keep decreasing, its rate now grows drastically, causing a huge amount of middle-class society being unable to purchase decent housing. This financial issue tends to embed a mindset in every individual’s mind that buying or building house permanently is an ineffective act. Thus, it will affect the building’s prestige as it is lowered and the aspects of a house are set aside. This statement can be proven by the fact that the resident’s incomes are quite low and the amount of money that can be allocated to purchase building materials are limited. Because of this, apartment’s purchasing rate has increased, especially those with low prices. With limited budget, residents are having a hard time to purchase high quality furniture. Based on that fact alone, a concept of compact and multifunctional furniture capable of fulfilling residents and user’s needs are greatly needed. This concept is refered as “Neutral Chameleon” where furnitures had to reach several qualities such as, economical and ergonomically fulfilled but in the mean time capable of adapting to user’s current layout situation.